Netizens' Responses to Theological Content on Social Media: A Case Study of Dondy Tan - Gerry Ismail Anrivika; Rifki Rosyad (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This research is motivated by the rapid development of digital communication, which has had a significant impact on social interaction patterns, including in the realm of da'wah (Islamic outreach), which is now often conducted online. One interesting figure to study is Dondy Tan, a content creator who actively uses YouTube to deliver da'wah. The content he presents not only conveys moral and religious messages but also often touches on fundamental theological issues, such as understanding divinity, interpreting holy books, and studying the history of religious development. The main focus of this research is to analyze how Dondy Tan constructs the argumentation flow in each of his da'wah content, as well as to examine how the audience, especially the netizen community, responds to and interprets the messages conveyed. This research uses a qualitative, descriptive-analytical approach. The primary data source is Dondy Tan's da'wah videos uploaded to his YouTube channel, which are then analyzed using Fairclough's discourse analysis framework. Furthermore, netizen comments in the discussion column are also studied, especially comments that generate a lot of responses, replies, and debate. The intense interaction in the comment space reflects the dynamics of digital communication and the construction of meaning for the da'wah messages conveyed.